Symposium Review: Drug Discovery, Design and Clinical Research in Academia - Vlaar, Cornelis P.; Hernández, Lesbia (Puerto Rico Health Sciences Journal, 2009)
The development of new drugs for the pharmacological treatment of diseases is a costly and time-consuming process. The pharmaceutical industry has traditionally played the main role in the discovery, development, manufacturing and marketing of new drugs. However, in recent years, the role of academia in the process of drug discovery and development, and its eventual translation into clinical applications has steadily increased. At the occasion of their 95th anniversary, the School of Pharmacy at the University of Puerto Rico organized a symposium titled "Drug Discovery, Development and Clinical Research in Academia". This article presents a summary of the symposium presentations and the potential role of academic drug discovery and development as a complement to the pharmaceutical manufacturing industry in Puerto Rico.